2021
DOI: 10.3390/ijms22020754
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Type-5 Inhibitor Tadalafil Modulates Steroid Hormones Signaling in a Prostate Cancer Cell Line

Abstract: Background: The androgen receptor (AR) plays a key role in normal prostate homeostasis and in prostate cancer (PCa) development, while the role of aromatase (Cyp19a1) is still unclear. We evaluated the effects of a treatment with Tadalafil (TAD) on both these proteins. Methods: Androgen-sensitive human PCa cell line (LnCAP) was incubated with/without TAD (10−6 M) and bicalutamide (BCT) (10−4 M) to evaluate a potential modulation on cell proliferation, protein and mRNA expression of Cyp19a, AR and estrogen rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 62 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…We demonstrated for the first time that tadalafil can modulate AR expression in prostate cancer cells in vitro. We also showed that tadalafil induces the stabilization and reduces the degradation of AR, that is more efficiently accumulated within the nucleus [30]. Interestingly, this effect could lead to a potential anti-cancer action of tadalafil by enhancing the therapeutic effect of ADT.…”
Section: Pde5i and Prostatementioning
confidence: 58%
See 3 more Smart Citations
“…We demonstrated for the first time that tadalafil can modulate AR expression in prostate cancer cells in vitro. We also showed that tadalafil induces the stabilization and reduces the degradation of AR, that is more efficiently accumulated within the nucleus [30]. Interestingly, this effect could lead to a potential anti-cancer action of tadalafil by enhancing the therapeutic effect of ADT.…”
Section: Pde5i and Prostatementioning
confidence: 58%
“…Moreover, in PCa cell lines, the AR antagonist bicalutamide (BCT) increased ARO expression and ERβ transcriptional activity; indeed, in CRPC ARO expression was significantly increased in tumor samples. Our study carried on with LnCAP cells, demonstrated for the first time that chronic exposure (48hrs) to BCT produced a significant increase in ARO mRNA, that was reverted by co-treatment with tadalafil [30]. The inhibition of PDE5 has been shown to induce anticancer effects [36] both in pre-clinical [37,38] and clinical experiences [39].…”
Section: Pde5i and Prostatementioning
confidence: 77%
See 2 more Smart Citations
“…RNA extraction was performed using TRIZOL according to the manufacturer's instructions, as previously described [22,23]. Treatment with DNAse enzyme was performed to remove genomic DNA contamination.…”
Section: Rna Extraction Reverse Transcription and Real-time Quantitat...mentioning
confidence: 99%